2015
DOI: 10.1186/s12889-015-2681-6
|View full text |Cite
|
Sign up to set email alerts
|

An ecological analysis of food outlet density and prevalence of type II diabetes in South Carolina counties

Abstract: BackgroundStudies suggest that the built environment with high numbers of fast food restaurants and convenience stores and low numbers of super stores and grocery stores are related to obesity, type II diabetes mellitus, and other chronic diseases. Since few studies assess these relationships at the county level, we aim to examine fast food restaurant density, convenience store density, super store density, and grocery store density and prevalence of type II diabetes among counties in South Carolina.MethodsPea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 37 publications
5
29
1
Order By: Relevance
“…However, the Swedish study was an aggregate-level analysis, since the participants' dwelling could only be geocoded at the level of small geographical units (that averaged 1000 participants per unit) and failed to adjust for key confounders, such as physical activity. Another countylevel ecological study 29 that used self-reported data in South Carolina, USA, reported no association between density of food outlets and county-level type 2 diabetes, subsequent to all adjustments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Swedish study was an aggregate-level analysis, since the participants' dwelling could only be geocoded at the level of small geographical units (that averaged 1000 participants per unit) and failed to adjust for key confounders, such as physical activity. Another countylevel ecological study 29 that used self-reported data in South Carolina, USA, reported no association between density of food outlets and county-level type 2 diabetes, subsequent to all adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported null or counterintuitive findings. 28,29 Most studies have been small in population size and geo graphical scale with relatively homogen eous populations and exposure characteristics, which has limited their statistical power and generalisability, and many were based on self-reported, survey-based measures. Further, most of the studies evaluating the association of food outlet accessi bility with chronic disease risks have been done in the USA, and there have been no studies that have examined the associations between accessibility to ready-to-eat food environments selling food that can be instantly consumed and type 2 diabetes at a national scale in the UK.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…Data for these measures were obtained from the U.S. Census Bureau's 2005–2009 American Community Survey (ACS) 5‐year Estimates. Measures of the health and healthcare context of counties included: the age‐adjusted percentage of adults (≥20 years) with obesity, the age‐adjusted percentage of adults (≥20 years) who were physically inactive, the number of outpatient visits per 1,000 people, the percentage of the population without health insurance, and the number of physicians per 1,000 people. Obesity and physical inactivity prevalence data for adults were obtained from the CDC's Diabetes Interactive Atlas.…”
Section: Methodsmentioning
confidence: 99%
“…While this is hopeful news, diabetes prevalence remains an important public health issue and requires continued research to further identify factors relevant to maintaining this progress . Ecological studies exploring diabetes prevalence in the U.S. have shown geographic clusters of high and low diabetes prevalence within single communities and among communities within a single state , as well as across the entirety of the U.S. . Among these studies, racial/ethnic populations and poverty , food environment measures , and local business or entrepreneurial culture have all been shown to be associated with diabetes prevalence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation